Komunikasi dalam Organisasi Perpustakaan - Nurul Hayati (Program Studi Ilmu Perpustakaan UIN Alauddin, 2014)
Library is one of social organizations and is always involved in any kind of communication. Communication is always occurred in each area in library, for instance, communication links to the top, bottom, and horizontal line. Communication is a process of sending ide or thoughts to others. Such communication is needed in order to have good circumstances in library, and those from outside the library.